2014
DOI: 10.1002/mus.23947
|View full text |Cite
|
Sign up to set email alerts
|

Nerve enlargement after cold exposure: A pilot study with ultrasound imaging

Abstract: These preliminary results revealed that cold exposure may cause acute nerve swelling. Further studies with larger samples will be necessary to confirm our findings, to correlate them with electrophysiological data, and to explore when/how the nerve edema resolves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 17 publications
0
11
0
1
Order By: Relevance
“…A recent preliminary study showed that cold exposure may cause swelling of the median nerve at the carpal tunnel inlet. 10 The average temperature in The Netherlands is much lower than in India. We did not measure body temperature in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent preliminary study showed that cold exposure may cause swelling of the median nerve at the carpal tunnel inlet. 10 The average temperature in The Netherlands is much lower than in India. We did not measure body temperature in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps this finding could be explained by differences in arm exercise, labor, race, or environmental factors. A recent preliminary study showed that cold exposure may cause swelling of the median nerve at the carpal tunnel inlet . The average temperature in The Netherlands is much lower than in India.…”
Section: Discussionmentioning
confidence: 99%
“…It is worthwhile noting that some studies have demonstrated that nerve size may be influenced by age, gender, body mass index and height 15 19. Temperature of the limb may also influence nerve calibre 22. As such, it is recommended that comparison groups in studies of nerve US are matched for those subject characteristics and standardised environmental conditions are employed during the study.…”
Section: Us Features Of Injured Peripheral Nervementioning
confidence: 99%
“…Hands were supported to be able to maintain a position of forearm supination, elbow flexion, and wrist extension in accordance with the technique. The cross‐sectional area was measured by the direct tracing method, with an electronic caliper from the inner border of the perineural echogenic rim from the swollen area just proximal to the entrapment area (Figure ) . The mean of 3 consecutive measurements was considered for statistical analyses.…”
Section: Methodsmentioning
confidence: 99%
“…entrapment area ( Figure 1). 10,11 The mean of 3 consecutive measurements was considered for statistical analyses.…”
Section: Cross-sectional Area Measurementmentioning
confidence: 99%